2023
DOI: 10.1021/jacs.3c01949
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Cyclopropanations with Nonstabilized Carbenes

Abstract: Cyclopropanes are common building blocks in pharmaceuticals, agrochemicals, and organic materials. The most general methods for the synthesis of chiral cyclopropanes are catalytic additions of diazoalkanes to alkenes. However, a limitation of this approach is that diazoalkanes can only be safely handled on preparative scales if they possess stabilizing substituents. Here we show that gem-dichloroalkanes can serve as precursors to nonstabilized carbenes for asymmetric cyclopropanation reactions of alkenes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…While its role has not been completely elucidated, zinc salts appear to accelerate the reduction of cobalt catalyst L1 CoBr 2 to L1 CoBr, which is required for initial catalyst activation and subsequent turnovers. It has been also reported that zinc halide may act as a Lewis acid in the catalytic cycle. , Omission of zinc halides or use of substoichiometric amounts resulted in reduced conversion. Unfortunately, we experienced reproducibility issues with different sources of zinc bromide as well as handling challenges because of its hygroscopicity.…”
Section: Resultsmentioning
confidence: 99%
“…While its role has not been completely elucidated, zinc salts appear to accelerate the reduction of cobalt catalyst L1 CoBr 2 to L1 CoBr, which is required for initial catalyst activation and subsequent turnovers. It has been also reported that zinc halide may act as a Lewis acid in the catalytic cycle. , Omission of zinc halides or use of substoichiometric amounts resulted in reduced conversion. Unfortunately, we experienced reproducibility issues with different sources of zinc bromide as well as handling challenges because of its hygroscopicity.…”
Section: Resultsmentioning
confidence: 99%
“…The use of dichloromethane and gem-dichloroalkenes as methylene and vinylidene precursors, with gold, cobalt and dinickel catalysis, has been reported-cycloaddition to enones and olefins, and cyclopropanation, was achieved. [15,16] We wondered whether gem-dihaloalkanes could be used-two gem-CÀ X bonds could be cleaved, with metals, to afford Fischertype metal carbene intermediates in couplings with two other/different substrates, resulting in the creation of two geminal bonds and subsequently affording prochiral tertiary and quaternary carbon centers. [17] We commenced our studies by exploring the possibility of using difluoroalkane 1 a in selectively coupling with a phenyl Grignard nucleophile and chlorosilane electrophile (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The coupling with NiCl 2 affords the phenylsilylated motif 4 a in 77 % GC yield (entry 13). However, the reactions are almost impeded when using catalysts such as MnCl 2 , MoCl 3 , WCl 6 , VCl 3 , and AgCl (entries [14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…2 The introduction of cyclopropane units into drug molecules can lead to significantly improved drug performance, including enhanced biological activity, bioavailability, half-life stability, and permeability. 3 A broad range of classic methods have been developed for the construction of functionalized cyclopropanes, 4 including the metal-catalyzed carbene insertion of terminal alkenes, 5 the Simmons–Smith cyclopropanation of allylic and homoallylic alcohols, 6 the Kulinkovich and Corey–Chaykovsky reactions, 7 and conjugate addition followed by the cyclization of activated alkenes. 8 These methods have been well established in previous studies.…”
mentioning
confidence: 99%